Motivasi Belajar Peserta Didik di Era New Normal - Mirzon Daheri; Wahyudi Wahyudi; Astuti Cendrawati Ramli; Hasmirati Hasmirati; Arisman Arisman; Muhammad Resky (Journal on Education, 2023)
Learning motivation is one of the most important factors owned by every student in order to get maximum results in a learning process at school. This study has a purpose, namely to determine the level of learning motivation in the new normal era in students of SMKS TP 45 Negara in 2022. The population in this study is students of XP1 and XP2 classes, totaling 70 people. The sampling technique in this study used a total sampling technique, where the entire population was used as a sample in this study. This research is a type of survey research using a quantitative descriptive design. The instrument used in this study was a questionnaire which consisted of 15 questions with a Likert scale which was adopted from previous research. The results in this study are the level of learning motivation in the low category as many as 4 people (5.7%), the medium category as many as 12 people (17.1), the high category as many as 22 people (31.4%), and the very high category as many as 32 people (45.7%). So it can be concluded that the average level of student learning motivation in SMKS TP 45 Negara in the new normal era is in the very high category.